Acute and Chronic Toxic Effects of Chloramphenicol, Erythromycin and Tetracycline on the Early Life Stage of Amphibian (Xenopus tropicalis) - Huang1, Hong; Liu2, Zhen; Yang2, Hongweni; Yin1, Daqiang (Asian Journal of Chemistry, 2013)
An acute and a chronic test with the tadpole embryos at stage 46 of amphibian (Xenopus tropicalis) were conducted to determine the toxic effects of chloramphenicol, erythromycin and tetracycline. In the acute test, both the percentage of survival and the whole body length were slightly decreased; the percentage of teratogenesis was increased compared with the control. The chloramphenicol and tetracycline had a higher percentage of teratogenesis than erythromycin. In the chronic test, the cumulative mortality was 11.7, 21.1 and 30.8 % in the treatment group with 1 mg/L of chloramphenicol, erythromycin and tetracycline, respectively. Three antibiotics can inhibit the growth of the embryos of X. tropicalis. The whole body length and the biomass were decreased and the developmental stages were also delayed. The chronic test with larvaes of X tropicalis was much more sensitive than the acute test. These findings may help to understand the potential biological effects of antibiotics on aquatics organisms.